RFID handbook : fundamentals and applications in contactless smart cards, radio frequency identification and near-field communication - Finkenzeller, Klaus (John Wiley &Sons, 2010)
This is the third revised edition of the established and trusted RFID Handbook; the most comprehensive introduction to radio frequency identification (RFID) available. This essential new edition contains information on electronic product code (EPC) and the EPC global network, and explains near-field communication (NFC) in depth